Effects of overexpression of a bHLH transcription factor on biomass and lipid production in Nannochloropsis salina. Issue 1 (December 2015) - Kang, Nam; Jeon, Seungjib; Kwon, Sohee; Koh, Hyun; Shin, Sung-Eun; Lee, Bongsoo; Choi, Gang-Guk; Yang, Ji-Won; Jeong, Byeong-ryool; Chang, Yong
Abstract Background Microalgae are considered promising alternative energy sources because they consume CO2 and accumulate large amounts of lipids that can be used as biofuel.Nannochloropsis is a particularly promising microalga due to its high growth rate and lipid content, and the availability of genomic information. Transcription factors (TFs) are global regulators of biological pathways by up- or down-regulation of related genes. Among these, basic helix-loop-helix (bHLH) TFs regulate growth, development, and stress responses in plants and animals, and have been identified in microalgae. We identified two bHLH TFs in the genome ofN. salina CCMP1776, NsbHLH1, andNsbHLH2, and characterized functions ofNsbHLH2 that may be involved in growth and nutrient uptake. Results We obtainedNsbHLH2 overexpressing transformants ofN. salina CCMP1776 by particle bombardment and confirmed that these were stable transformants. Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting using antibodies against the FLAG tag that was attached at the end of the coding sequence confirmed the expression of the NsbHLH2 protein under various culture conditions. The qRT-PCR results also indicated that the endogenous and transgenic expression ofNsbHLH2 was reduced under stressed conditions. Overexpression ofNsbHLH2 led to increased growth rate in the early growth period, and concomitantly higher nutrient uptake, than wild type (WT). These enhanced growth and nutrient uptake resulted in increased productivities of biomass and FAME. For example, one of the transformants, NsbHLH2 3–6, showed increased biomass productivity by 36 % under the normal condition, and FAME productivity by 33 % under nitrogen limitation condition. Conclusively, the improved growth in the transformants can be associated with the enhanced nutrient uptake. We are currently assessing their potential for scale-up cultivation with positive outcomes. Conclusion Overexpression ofNsbHLH2 led to enhanced growth rate and nutrient uptake during the early growth phase, and increased biomass and FAME productivity, especially in the later period under normal and stressed conditions. Based on these results, we postulate thatNsbHLH2 can be employed for the industrial production of biodiesel fromN. salina .